Crashworthiness behavior of aluminum profiles with holes considering damage criteria and damage evolution. (October 2017) - Estrada, Quirino; Szwedowicz, Dariusz; Silva-Aceves, Jesús; Majewski, Tadeusz; Vergara-Vazquez, Julio; Rodriguez-Mendez, Alejandro
Highlights: The effect of discontinuities in aluminum profiles considering damage evolution is investigated. The importance of failure models with the evolution to modeling of light structures was corroborated. Improvements of crashworthiness performance of profiles were obtained by discontinuities. A rule for the effective sizing of the hole diameter was specified. A specific automotive application is presented, demonstrating the usefulness of the current study. ABSTRACT: In this paper the commercial finite element software Abaqus was employed to analyze the effect of mechanical discontinuities on the crashworthiness performance of aluminum profiles. Special emphasis was placed on material damage and its evolution during a crash event. The discontinuities were located at different heights on two opposite walls of aluminum profiles. During the crash simulations, the profiles were subjected to axial impact loads using a 500 kg rigid body striker with an initial velocity of 10 m/s. The ductile material properties of aluminum alloys were considered using the shear, ductile and Müschenborn–Sonne Forming Limit Diagram (MSFLD) damage initiation criteria in the discrete models. In order to model the progressive failure and removal of finite elements, damage evolution option was applied. In all cases, the implementation of discontinuities shows a reduction of peak load (Pmax ) of up to 4.74% with respect to a profile without discontinuities. In the same way, an increase in energy absorption (Ea ) and crush force efficiency (CFE) of 7% and 12.69% respectively, was observed. It was found that the implementation of discontinuities increases the crashworthiness performance of the aluminum profiles. Moreover, the best location for the discontinuities was at the top of the walls of the structure. Following this finding, a typical application in automotive crashworthiness design was demonstrated successfully. Graphical abstract: